Atom economic closed-loop recycling of thermoset polyurethane foams - Zenghe Liu; Ling Liu; Yangfei Li; Kexuan Yang; Sujing Li; Wei Li; Yutian Zhu; Tao Xie (Nature Communications)
Abstract Thermoset polyurethane foams are extensively used in industrial and consumer products, but their end-of-life recycling has been a long-standing challenge. Closed-loop recycling represents an idea solution, but its practical value is often compromised due to the consumption of catalyst and/or solvent as well as degradation in the recycled material properties. Here, we report an efficient foam-to-foam closed-loop recycling strategy that addresses these issues. Our approach relies on the inherent equilibrium nature of the covalent bonds in the polyurethane network. Addition of acetoxime shifts the equilibrium to dissociate the covalent bonds, which transforms a monolithic foam into surface functionalized micro-particles. By removing acetoxime via evaporation, the original covalent bonds are reformed and these micro-particles are rejoined to form a new foam with acetoxime as the porogen. The process employs neither catalyst nor solvent and the only chemical reagent involved (acetoxime) is fully recoverable. Importantly, the process yields new foams with mechanical properties identical or even superior to the original foam. Our strategy of achieving atom economic recycling of polyurethane foams is potentially applicable to other thermosets.